(untitled) (Global Journal of Human-Social Science, 2012)
Background : Cross border-trade has been seen to have gender dimension. Women are seen to be engaged in informal cross-border trade along the borders. Most times women are facing a lot of challenges in trying to transport their goods from customs officials and other security agents. Despite these difficulties, they still engage in this informal trade along this border. This paper examines the coping strategies of women involved in informal cross-border trade. Methods : This study is based on Focus Group Discussion (FGDs) conducted with 50 informal traders, in-depth-interviews conducted with security agents and drivers along Lagos-Seme border.